2011
DOI: 10.1242/jcs.086488
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Chk1 prevents premature mitotic entry

Abstract: SummaryChk1 inhibits the premature activation of the cyclin-B1-Cdk1. However, it remains controversial whether Chk1 inhibits Cdk1 in the centrosome or in the nucleus before the G2-M transition. In this study, we examined the specificity of the mouse monoclonal antiChk1 antibody DCS-310, with which the centrosome was stained. Conditional Chk1 knockout in mouse embryonic fibroblasts reduced nuclear but not centrosomal staining with DCS-310. In Chk1 +/myc human colon adenocarcinoma (DLD-1) cells, Chk1 was detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 41 publications
(71 reference statements)
2
37
1
Order By: Relevance
“…Likewise, the reported Cep63-dependent presence of Cdk1 at centrosomes [138] is almost certainly due to antibody cross-reactivity with Cep152 [139]. Thus, when interpreting immunocytochemical data reporting on unexpected centrosome-associations of particular proteins, it would seem wise to consider carefully the possibility of antibody-related artefacts [135,137,139,140]. Not only have proteins with well-established functions in DNA damage response pathways been reported to reside at centrosomes, but the opposite is also true: genuine centrosomal proteins have been implicated in DNA damage response.…”
Section: Centrosomes As Signalling Platforms In Vertebrates? (A) Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the reported Cep63-dependent presence of Cdk1 at centrosomes [138] is almost certainly due to antibody cross-reactivity with Cep152 [139]. Thus, when interpreting immunocytochemical data reporting on unexpected centrosome-associations of particular proteins, it would seem wise to consider carefully the possibility of antibody-related artefacts [135,137,139,140]. Not only have proteins with well-established functions in DNA damage response pathways been reported to reside at centrosomes, but the opposite is also true: genuine centrosomal proteins have been implicated in DNA damage response.…”
Section: Centrosomes As Signalling Platforms In Vertebrates? (A) Cellmentioning
confidence: 99%
“…These data implicated Chk1 in the spatio-temporal regulation of cell division and, moreover, raised the possibility that the centrosome-associated pool of this enzyme might contribute to mediate the DNA-damageinduced inhibition of Cdk1/cyclin B. However, a subsequent study irrefutably showed that the reported centrosomal localization of Chk1 could be attributed to cross-reactivity of one particular antibody with a newly identified centrosomal protein, and that nuclear Chk1, not centrosomal Chk1, regulates Cdk1/cyclin B [137]. Likewise, the reported Cep63-dependent presence of Cdk1 at centrosomes [138] is almost certainly due to antibody cross-reactivity with Cep152 [139].…”
Section: Centrosomes As Signalling Platforms In Vertebrates? (A) Cellmentioning
confidence: 99%
“…This link had been anticipated by reports that centrosomal Chk1 played a critical role in determining the timing of mitotic commitment. However, concerns about the specificity of the antibody used for immunolocalization and the expression levels of centrosomally targeted Chk1 fusion proteins in the early studies has questioned whether Chk1 does indeed act at centrosomes (Matsuyama et al 2011). Thus, the link between pericentrin and cell-cycle control remains enigmatic, although it is tempting to speculate that the potential coupling between fission yeast pericentrin and Cut12/Polo Plo1 controls could hold the key (Fong et al 2010).…”
Section: The Centrosome and Its Duplication Cyclementioning
confidence: 99%
“…Cells derived from MOPDII patients with PCNT mutations exhibit defective ATR signalling and a marked reduction in the centrosomal pool of CHK1 [60,93]. Although the precise role of this pool remains controversial, reduced centrosomal CHK1 levels correlate with premature activation of cyclin B-CDK1 in pericentrindeficient cells [60,98,99]. Thus, anti-proliferative effects of replicative stress and premature CDK1 activation could contribute to the global growth failure seen in PD patients.…”
Section: Centrosomes and Body Size (A) Primordial Dwarfism Syndromesmentioning
confidence: 99%